Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan Penularan Covid-19 pada Masyarakat - Iin Patimah; Sri Yekti W; Rudy Alfiansyah; Hasbi Taobah; Devi Ratnasari; Andri Nugraha (Jurnal Kesehatan, 2021)
The number of Covid-19 in various countries continues to increase every day, various efforts have been made by the government in various countries, one of which is in Indonesia, one of the efforts that have been made is education. Education is the first step to form behavior that can reduce the spread of Covid-19. The purpose of this research is to find out whether there is a relationship between knowledge about the prevention of transmission of Covid-19 with prevention behavior of transmission of Covid-19 in the community in the Garut district. This type of research is a cross-sectional study, using data collected online based on reports from 145 respondents. The research data were analyzed using the chi-square to assess the relationship between knowledge and behavior. The results showed that more than half of the respondents already had good knowledge, namely 77,2%, and 67% of respondents have good behavior. From the results of statistical tests obtained p-value 0,06 (>0,05), it can be concluded that there is no significant relationship between the level of knowledge about the prevention of Covid-19 and the behavior to prevent the spread of Covid-19. Given that there are several findings in research and limitations in the study, therefore, it is hoped that in the future various parties can examine other factors related to the level of knowledge about and behavior to prevent the spread of Covid-19 in various communities in various regions, districts, cities and countries.